Collective phenomena at the metal-plasma interface; The 28th IEEE International Conference on Plasma Science and 13th IEEE International Pulsed Power Conference, Las Vegas, NV, june 17-22, 2001 - Mesyats G. A. Gennady Andreyevich (2001, 2001)
В фонде НТБ ТПУ отсутствует